Selectively bred oysters can alter their biomineralization pathways, promoting resilience to environmental acidification. (25th September 2019) - Fitzer, Susan C.; McGill, Rona A. R.; Torres Gabarda, Sergio; Hughes, Brian; Dove, Michael; O'Connor, Wayne; Byrne, Maria
Abstract: Commercial shellfish aquaculture is vulnerable to the impacts of ocean acidification driven by increasing carbon dioxide (CO2 ) absorption by the ocean as well as to coastal acidification driven by land run off and rising sea level. These drivers of environmental acidification have deleterious effects on biomineralization. We investigated shell biomineralization of selectively bred and wild‐type families of the Sydney rock oyster Saccostrea glomerata in a study of oysters being farmed in estuaries at aquaculture leases differing in environmental acidification. The contrasting estuarine pH regimes enabled us to determine the mechanisms of shell growth and the vulnerability of this species to contemporary environmental acidification. Determination of the source of carbon, the mechanism of carbon uptake and use of carbon in biomineral formation are key to understanding the vulnerability of shellfish aquaculture to contemporary and future environmental acidification. We, therefore, characterized the crystallography and carbon uptake in the shells of S. glomerata, resident in habitats subjected to coastal acidification, using high‐resolution electron backscatter diffraction and carbon isotope analyses (as δ 13 C). We show that oyster families selectively bred for fast growth and families selected for disease resistance can alter their mechanisms of calcite crystal biomineralization, promoting resilience to acidification. The responses of S. glomerata to acidification in their estuarine habitat provide key insights into mechanisms of mollusc shell growth under future climate change conditions. Importantly, we show that selective breeding in oysters is likely to be an important global mitigation strategy for sustainable shellfish aquaculture to withstand future climate‐driven change to habitat acidification. Abstract : We characterized the crystallography and carbon uptake in the shells of the oyster Saccostrea glomerata being farmed in habitats subjected to acidification from land run‐off using high‐resolution electron backscatter diffraction and carbon isotope analyses (δ 13 C). Environmental carbon was linked with the changing carbon in the shell and differences in shell growth and crystallography across oyster families selectively bred for fast growth or disease resistance. We show that these oyster families can alter their mechanisms of biomineralization, promoting resilience to coastal acidification. Selective breeding in oysters is likely to be an important global mitigation strategy for sustainable aquaculture.